Rodzaje dekoncentracji wewnętrznej w materialnym prawie administracyjnym - Górka, Marta (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Internal deconcentration is intended to be an institution which is optional - a public authority may, or may not use it. However, there are cases in which the legislator departs from the optional forms of internal deconcentration and gives it mandatory. In addition to internal deconcentration optiona and mandatory we still dealing with an internal deconcentration under the agreement and statutory internal deconcentration. Internal deconcentration is the institution through which public administration is able to respond to current challenges and social expectations, which is why the legislator has introduced a variety of its types
Keywords: dekoncentracja wewnętrzna fakultatywna; dekoncentracja wewnętrzna ustawowa; dekoncentracja wewnętrzna na mocy porozumienia; upoważnienie administracyjne; dekoncentracja wewnętrzna; dekoncentracja wewnętrzna obligatoryjna